Shifting policy perspectives: revelatory incident narratives from physical education stakeholders. Issue 3 (2nd September 2022) - Lorusso, Jenna R.; Scanlon, Dylan; MacPhail, Ann; Hargreaves, Suzanne; Storey, Mike; Dabbagh, Lara
ABSTRACT: Widely held traditional policy perspectives within physical education, and the linear and top-down assumptions about policy processes associated with them, arguably limit the perceivable scope of policy engagement possibilities, particularly for front-line policy actors. To illuminate this assertion, we utilised the revelatory incident technique. We present co-constructed narratives of key incidents through which some members of our group of physical education stakeholders shifted from holding more traditional to more complex policy perspectives. Our analysis of these revelatory incident narratives illustrates how complex policy perspectives, which emphasise the messy, unpredictable, and multi-directional nature of policy processes, arguably allow for an expanded view of how policy processes can be engaged with by all physical education policy actors, especially those on the front-line.